Nutrition and physical activity in Asian Indians with non-alcoholic fatty liver: A case control study. Issue 2 (March 2019) - Bhatt, Surya Prakash; Misra, Anoop; Nigam, Priyanka
Abstract: Aim: We tested the hypothesis that Asian Indians with non-alcoholic fatty liver disease (NAFLD) would have imbalanced diets and lower intensity of physical activity than those without NAFLD. Methods: We studied dietary intake, intensity of physical activity and anthropometric and metabolic profiles in subjects with NAFLD and in healthy controls. Complete clinical, biochemical, dietary and physical activity profiles were studied for 169 cases and 173 controls in a prospective manner. Bivariate and multivariate analyses were carried out to identify the predictors of NAFLD [odds ratio (OR) and 95% confidence intervals (95%CI)]. Results: The mean dietary intakes of total energy, carbohydrate, protein, total fat, saturated fat and total cholesterol were significantly higher, while intake of monounsaturated fatty acids and polyunsaturated fatty acids was significantly lower in cases as compared to controls (p < 0.01 for all). Further, mean physical activity in a day (expressed as MET.Minutes) and total energy expenditure were significantly lower in cases than in controls (33.3 ± 3.6 vs. 36.2 ± 0.5, p = 0.001 and 2707.6 ± 505.6 vs. 2904.3 ± 690.3, p = 0.02, respectively). On multivariate analysis, percentage dietary total fat intake (OR: 13.4; 95% CI: 4.6–39.3, p = 0.001), homeostatis model assessment for insulin resistance (OR: 6.9; 95% CI: 3.2–14.8, p = 0.001) abdominal obesity (OR: 2.7; 95% CI: 1.5–5.0, p = 0.001) and high serum triglycerides (OR: 2.1; 95%CI: 1.2–3.8, p = 0.007) were associated with an increased risk for development of NAFLD. Conclusion: Decrease in intake of total dietary fats and improvement of insulin resistance, abdominal obesity and blood triglycerides should be important measures for management of NAFLD in Asian Indians in north India. Highlights: Dietary fat intake, along with component of the metabolic syndrome was independent risk factor for NAFLD. hs-CRP levels in persons with NAFLD was independent of obesity and abdominal obesity. Higher intakes of energy, carbohydrate, SFA, n-3 PUFAs and lower intake of MUFAs and n-6 PUFAs were observed in NAFLD.